Parâmetros reprodutivos e alimentares da abelha solitária Epanthidium tigrinum (Schr.) (Hymenoptera, Megachilidae) para criatório racional - Muniz, Vitória Inna Mary de Sousa (2021)
Epanthidium tigrinum is bee native bee Brazil showing potential to be used for pollination in agricultural crops. However, the little information about their reproductive and feeding habits has prevented the breeding and management of these bees in a rational way. This study aimed to investigate the acceptance of trap nests, nesting and the influence of seasonality over an annual cycle on the nesting of E. tigrinum and on the food it provides for their young and the implications of these aspects on the potential of bee management. Trap nests were made in eight different diameter classes and offered to bees. The females were monitored daily to monitor the foundation and closure of the trap nests in each diameter class. The completed nests were kept at room temperature in the same place of the experiment until the emergence of adult bees. Data on seasonality in the construction of the nests, architecture of the nests, rate of emergence of the offspring, sex ratio, mortality and diet of the immatures through pollen analysis of fecal waste were obtained and analyzed. The results showed that E. tigrinum nests well in trap nests with diameters between 0.45 and 0.55 cm, it does not present seasonality producing generations all year round, but the temperature has a direct effect on its reproductive success. The sex ratio was shifted to females. The analysis of the trophic niche showed that this bee is polyletic, however, it has the capacity to expand or restrict its niche, according to the availability of resources in the environment. Through the analysis of the interaction networks, it was possible to visualize that E. tigrinum establishes a greater number of interactions in the post-rainy period, with interactions with the species Byrsonima crassifolia (nance) and Vigna unguiculata (cowpea) predominating. The availability of resources had a subtle effect on the nesting rate of bees, related to the participation of nance pollen in the diet. It is possible to conclude that E. tigrinum presents potential for breeding and management on a large scale, provided that the reproductive and feeding parameters indicated in this study are met